Star Wars. The last Jedi [videorecording (Blu-Ray)] - Johnson, Rian; Hamill, Mark; Fisher, Carrie; Driver, Adam; Ridley, Daisy, 1992- (Lucasfilm Ltd, 2019)
The Skywalker saga continues as the heroes of The Force Awakens join the galactic legends in an epic adventure. Having taken her first steps into the Jedi world, Rey joins Luke Skywalker on an adventure with Leia, Finn and Poe that unlocks mysteries of the Force and secrets of the past.